PvdA-bestuur. V.l.n.r. : Uijen, Reuvekamp, Heyne den Bak, Ouwerkerk, Van der Doef, Van den Bergh - Troost, Roel,
PvdA-bestuur. V.l.n.r. : Uijen, Reuvekamp, Heyne den Bak, Ouwerkerk, Van der Doef, Van den Bergh.